Empowering Arabic learners to make meaning: A genre-based approach. (November 2020) - Abdel-Malek, Myriam
Abstract: Motivated by the increase in students' enrollment in Arabic as a foreign language (AFL) classes and a lack of specified pedagogies aligned with the American Council on the Teaching of Foreign Languages Performance Guidelines for Language Learners (ACTFL, 2017 ), this study investigated a genre-based approach (GBA) informed by systemic functional linguistics (SFL) to teach and assess the written Arabic recount of habitual events. The purpose of this article is to show how the GBA empowered novice Arabic learners to make meaning when portraying the main participant in the written Arabic recount of habitual events. The study quantitatively observed the changes in the writing of 15 students over the course of a unit of study, and qualitatively an in-depth observation of two students using SFL as the framework for analysis. The results indicate that the students improved on using interpersonal meanings to portray the main participant associated with the Arabic written recount of habitual events. The results suggest that SFL genre-informed pedagogy empowers AFL students to expand their linguistic repertoire to address the socio-culturally purpose of the recount of habitual events. Further implications on the teaching of AFL learners and on AFL pedagogy will be discussed. Highlights: Grammar is meaning. Genre pedagogy fosters form-function relationship. Genre pedagogy addresses the Arabic learners' primary motivation to study the language, that is, pragmatic and functional.